الفرق بين الوجوب ووجوب الأداء عند الإمام الزركشي (دراسة أصولية مقارنة) (Journal of Imam Al-Kadhim College, 2023)
Praise be to God, by whose grace good deeds are accomplished, and may blessings and peace be upon our Prophet Muhammad and his family and companions, and after: The issue of fundamentalist differences is one of the most important topics that scholars of assets have taken care of, as it removes forms and removes the confusion between many fundamentalist terms that are almost similar in appearance to a large extent and differ in their essence. and its meaning Which results in a difference in the rulings based on them, so there is a great need here to define the limits and differentiate between the limited, so the scholars of the origins were interested in mentioning the differences in separate places of their works when there are forms or similarities between two similar terms, the research dealt with the difference between the obligation and the obligation to perform according to Imam Al-Zarkashi A comparative fundamental study He concluded with a number of results, the most important of which are: Imam al-Zarkashi did not differentiate between obligation and obligation of performance, which is the doctrine of most scholars, and some Hanafi masters differentiate between obligation and obligation of performance, and that the distinction between them has an impact on the rulings based on each of the two terms.
Keywords: الكلمات المفتاحية : الوجوب , وجوب الاداء, الزركشي